Comparison of Oral Sodium Phosphate and Warm Water Enema for Bowel Preparation Prior to Double-Contrast Barium Enema: A Prospective Randomized Clinical Trial - Rotjana-aree, Benjaporn; Suang-yanont , Kanita; Neurplub, Pattaraporn (Lampang Medical Journal, 2022)
Background: Double-contrast barium enema (BE) is a common radiological study for colonic evaluation. Adequate colonic preparation is essential for the accurate interpretation and could be done by either enema or oral laxatives. Oral sodium phosphate (OSP) is an interesting laxative agent and well known for cleaning bowel prior to colonoscopy. It has not been used for BE in Srisangworn Sukhothai Hospital. Objective: To compare quality of bowel preparation for BE between 3 methods; OSP, warm water enema, and OSP combined with enema. Material and Method: A prospective randomized clinical trial was conducted on 45 patients who underwent BE at Srisangworn Sukhothai Hospital between February and August 2008. The patients were equally allocated into 3 groups of bowel preparation methods by randomization; group 1 OSP , group 2 warm water enema and group 3 OSP combined with warm water enema. Demographic data, amount of OSP administration, number of enema and bowel evacuation were recorded. The level of bowel cleanness and quality of interpreted films were evaluated by one radiologist using 5-leveled grading system for colon cleansing. One way ANOVA and exact probability test were used for statistical analysis. Results: Eighteen patients were male and 27 were female. The mean age was 52 years (range, 24-74). The quality of interpreted films and demographic data were not significantly different between 3 groups, except the mean age and waist circumference were higher in group 2 (p=0.033 and 0.011 respectively). OSP alone or combined with enema caused more frequency of bowel evacuation than warm water enema alone (p<0.001). No significant difference of colonic cleanness among 3 groups was demonstrated (p=0.108) when using 5-leveled grading system. Re-classified evaluation into 2 classes, acceptable (grade 3-4) and unacceptable (grade0-2), resulted less favorable cleanness in warm water enema alone group than the others (p=0.02). Subgroup analysis between OSP alone and OSP combined with enema found no significant difference (p=0.651). Conclusion: OSP preparation, either using alone or combined with warm water enema, did not provide significant difference for bowel cleaning quality prior to barium enema. Both methods resulted in more favorable cleanness than warm water enema alone. OSP was the appropriate choice in routine bowel preparation for barium enema.